THE MODULAR SOLUTIONS OF INTERMODAL TERMINAL (Perner's Contacts, 2015)
The first part of the paper analyzes several new proposals to modular terminal solutions and their influences to technology of transshipment. The aim is to compare the individual technologies, one of them selected and introduced to the modular intermodal terminal. In conclusion the author provides an evaluation of suggested proposal solutions, mainly focusing on technological.
Keywords: terminal, intermodal transport, modular, portal crane, reachstacker